Impact of Lymphovascular Invasion on Survival Outcome in Patients With Gastric Cancer: A Retrospective Cohort Study. Issue 6 (8th March 2020) - Mei, Di; Zhao, Bochao; Zhang, Jiale; Luo, Rui; Lu, Huiwen; Xu, Huimian; Huang, Baojun
Abstract: Objectives: To evaluate the prognostic significance of lymphovascular invasion (LVI) for patients with gastric cancer (GC). Methods: A total of 1, 720 consecutive patients who underwent curative gastrectomy were retrospectively identified. The association between LVI and clinicopathologic characteristics was determined and its impact on survival outcome was evaluated. Results: LVI was detected in 21.3% of GC patients, 5.9% of patients with early GC, 24.0% of patients with advanced GC, and 6.7% of node-negative patients using H&E staining. Tumor size (odds ratio [OR], 1.509; 95% confidence interval [CI], 1.159-1.965; P < .01), differentiated type (OR, 1.817; 95% CI, 1.377-2.398; P < .001), and the depth of tumor invasion (OR, 3.011; 95% CI, 2.174-4.171; P < .001) were independent predictive factors for LVI. LVI-positive patients have a poorer prognosis than LVI-negative patients, irrespective of tumor stage or lymph node metastasis. LVI was an independent prognostic factor for patients with GC (hazard ratio, 1.299; 95% CI, 1.112-1.518; P < .001). Conclusions: LVI provided additional prognostic information for GC patients, and LVI-positive patients should be considered candidates for adjuvant chemotherapy.